Giant metastatic small bowel and mesentery localization and pleural metastases secondary to breast cancer. Case Report - De Bernardis, B.; Torresini, G.; Marinelli, S. (Acta Biomedica Atenei Parmensis, 2003)
The authors present a case of a patient with double metastatic abdominal and thoracic localization coming from breast cancer. Peculiarity of this case concerns both the considerable size of metastatic abdominal mass (11 centimetres of the major axis for a weight of almost half a kilogramme) and the swift development of the relapses at distance, even in the presence of an original tumour at first stage. Both abdominal surgical operation of the removal of the mass and diagnostic video assisted thoracoscopy (VAT) are described.